Colorectal cancer in the young: a possible role for immune surveillance?. Issue 1 (2nd January 2018) - Fiorot, Alain; Pozza, Anna; Ruffolo, Cesare; Caratozzolo, Ezio; Bonariol, Luca; D'Amico, Francesco Enrico; Padoan, Luigi; Calia di Pinto, Francesco; Scarpa, Marco; Castoro, Carlo; Bassi, Nicolò; Massani, Marco
Abstract: Background: Younger patients with colorectal cancer (CRC) generally have better survival in spite of worse clinical and pathological features. Methods: Twenty-six patients under 50 years operated for primary CRC were enrolled and matched 1:2:2 according to stage, tumor site and gender with 52 patients from 50 to 70 years and 52 patients over 70 years old. Results: Patients under 50 years had a significantly longer overall, cancer specific and disease free survival ( p  = .001, p  = .007 and p  = .05, respectively). However, they had more frequently lymphovascular invasion ( p  = .006) and they more frequently developed metachronous CRC at follow-up ( p  = .03). Nevertheless, preoperative lymphocytes blood count/white blood count (LBC/WBC) ratio inversely correlated with age at operation (rho = −.21, p  = .04) and it predicted CRC recurrence with an accuracy of 70%, p  < .001 (threshold value LBC/WBC = 0.21%) and better overall, cancer specific and disease free survival ( p  < .0001 for all). At multivariate analysis, stage and LBC/WBC ratio resulted independent predictors of disease free survival ( p  = .0001 and p  = .01, respectively). Conclusions: Patients under 50 years had a significantly longer survival with a higher LBC/WBC ratio. These results could suggest a possible role of immunosurveillance in neoplastic control.